Reading The Sign and Marker of Friendship in The Movie The Guys - Alifa Johariyah Ulfah (Cinematology: Journal Anthology of Film and Television Studies, 2021)
This study describes a semiotika research with the theory that Charles Sanders Pierce, with his main object is a film titled The Guys. The film is raised by the author because it is interesting, and many things that are a sign with the contents of the film explaining a friendship that struggled together to achieve their respective goals. This article aims to find out a marker sign in the film and the meaning contained. This research used a descriptive qualitative method. With qualitative methods and technical analysis of semiotika data in the film, this guys collected. In this study, the authors discovered the 17 that appeared and could be interpreted as a sign with the theory of Charles Sanders Pierce through his object angle (icon, index, and symbols).In this study discussed three main points of semiotika seen from the perspective of their objects, index and symbols. as for the icon to discusses the signs and markers are simultaneously, index discusses the reason, and symbols is a natural relationship between the signs and markers. Research suggests that each is done can be a meaning and a sign of a goal. Because no one is a sign except interpreted as a sign. This research can be a reference for the next research in the context of semiotic analysis choosing a film as a research subject. According to the results of the semiotika study, they carried the object that became very interesting, because it appears that the development of the film is so rapidly and fast to attract and be able to move the audience.